Differential Strategies to Tolerate Flooding in Polygonum hydropiper Plants Originating From Low- and High-Elevation Habitats - Chen, Xin-Sheng; Li, Ya-Fang; Cai, Yun-He; Xie, Yong-Hong; Deng, Zheng-Miao; Li, Feng; Hou, Zhi-Yong (Frontiers in Plant Science, 2019)
In species that occur over a wide range of flooding conditions, plant populations may have evolved divergent strategies as a consequence of long-term adaptation to local flooding conditions. In the present study, we investigated the effects of a flooding gradient on the growth and carbohydrate reserves of Polygonum hydropiper plants originating from low- and high-elevation habitats in the Dongting Lake wetlands. The results indicated that shoot length did not differ, whereas the total biomass and carbohydrate reserves were reduced under flooded as compared to well-drained conditions for plants originating from both habitat types. However, shoot length, shoot mass, rhizome mass, and total biomass were lower in plants from low-elevation habitats than in those from high-elevation habitats in the flooded condition. Soluble sugar and starch contents in belowground biomass were higher in plants from low-elevation habitats than in those from high-elevation habitats independently of the water level. Therefore, P. hydropiper plants from low-elevation habitats exhibit a lower growth rate and more conservative energy strategy to cope with flooding in comparison with plants from high-elevation habitats. Differential strategies to cope with flooding among P. hydropiper populations are most likely a response to the flooding pressures of the habitat of origin, and may potentially drive ecotype differentiation within species along flooding gradients.